Accurate quantification of the algebraic, multiplicative algebraic, and simultaneous iterative reconstruction techniques in ionosphere rebuilding based on the TIEGCM assessment - Ao Qi; HaiBing Ruan (Earth and Planetary Physics)
The algebraic reconstruction technique (ART), multiplicative algebraic reconstruction technique (MART), and simultaneous iterative reconstruction technique (SIRT) are computational methodologies extensively utilized within the field of computerized ionospheric tomography (CIT) to facilitate three-dimensional reconstruction of the ionospheric morphology. However, reconstruction accuracy elicits recurrent disputes over its practical application, and people usually attribute this issue to incomplete and uneven coverage of the measurements. The Thermosphere Ionosphere Electrodynamics General Circulation Model (TIEGCM) offers a reasonable physics-based ionospheric background and is widely utilized in ionospheric research. We use the TIEGCM simulations as the targeted ionosphere because the current measurements are far from able to realistically reproduce the ionosphere in detail. Optimized designations of satellite measurements are conducted to investigate the limiting performance of CIT methods in ionospheric reconstruction. Similar to common practice, electron density distributions from outputs of the International Reference Ionosphere (IRI) model are used as the iterative initial value in CIT applications. The outcomes suggest that despite data coverage, iterative initial conditions also play an essential role in ionospheric reconstruction. In particular, in the longitudinal sectors where the iterative initial height of the F2-layer peak electron density (hmF2) differs substantially from the background densities, none of the three CIT methods can reproduce the exact background profile. When hmF2 is close but the ionospheric F2-layer peak density (NmF2) is different between the targeted background and initial conditions, the MART performs better than the ART and SIRT, as evidenced by the correlation coefficients of MART being above 0.97 and those of ART and SIRT being below 0.85. In summary, this investigation reveals the potential uncertainties in traditional CIT reconstruction, particularly when realistic hmF2 or NmF2 values differ substantially from the initial CIT conditions.